Adolescents in residential treatment: The prevalence of ACEs, substance use and justice involvement. Issue 3 (3rd August 2020) - Schauss, Eraina; Zettler, Haley; Naik, Surabhi; Ellmo, Frances; Hawes, Kiersten; Dixon, Paige; Bartelli, Debra; Cogdal, Pam; West, Steven
Abstract: Although associations between developmental trauma, juvenile justice involvement and youth substance use have been previously reported in the published literature, the interconnection among these three factors has not been adequately studied. This article describes the interconnection among these three factors and calls for greater attention to the role of adverse childhood experiences (ACEs) in the diagnosis and treatment of youth who present with histories of substance use and/or offending behavior. Pilot data are presented that show high rates of self-reported trauma exposure, substance use history, justice involvement, and mental health problems in a sample of adolescents in residential treatment. The data point to the need for residential treatment centers to consider trauma histories in developing treatment plans for youth with current and prior substance use and offending behavior.